Creating a dementia enabling university using a Knowledge Translation approach: Innovative practice. (January 2021) - Phillipson, Lyn; Fleming, Richard; Swaffer, Kate; Steele, Linda; Sheridan, Lynnaire; Burns, Shawn; Cappetta, Kara; Cridland, Elizabeth
Universities can promote social impact by developing a dementia literate workforce. The Dementia Enabling University Strategy utilised a knowledge translation framework in an Australian university to inspire and support academics to engage students and consider how their skills and knowledge could contribute to the creation of more supportive environments for people with dementia. Dementia Enabling University Strategy ran across eight disciplines: law, media, social sciences, public health, engineering, business, marketing and psychology and was successful in engaging university academics and students. However, a longer term strategy is needed to embed 'dementia' as core business to the university impact agenda.